Организация геопорталов и ГИС систем на базе хранилища пространственных данных - Андреев, С.М.; Лысенко, В.Н.; Радчук, Вит. В.; Радчук, И.В. (Екологічна безпека та природокористування, 2012)
The approach to the organization of GIS and geoportals based on storage of spatial data and OLAP-technology of multivariate data analysis that deals with geodata collection, storing and analyzing is offered.